Developmental delay, intellectual disability, short stature, subglottic stenosis, hearing impairment, onychodysplasia of the index fingers, and distinctive facial features: A newly reported autosomal recessive syndrome. Issue 8 (2nd July 2020) - Mégarbané, André; Hana, Sayeeda; El‐Hayek, Stephany; Gambarini, Alicia; Al‐Ali, Mahmoud Taleb; Delague, Valérie
Abstract: We report on a multiply consanguineous Syrian family where two siblings, a boy and a girl, presented with a compilation of symptoms including developmental delay, severe intellectual disability, absent speech, hearing impairment, short stature, subglottic stenosis, increased length of the palpebral fissures, onychodysplasia of index fingers, scoliosis, genu valgum, and malpositioned toes. Two other individuals from the extended family with similar clinical features are also described. Array‐CGH did not reveal any pathological copy number variation. Exome sequencing failed to find any causal variants. Differential diagnoses and the possibility that we might be reporting a hitherto unknown syndrome are discussed.